Congenital toxoplasmosis and auditory disorders: a literature review - Ferreira, Laís; Sanfins, Milaine Dominici; Pinto, Julia Dalcin; Skarzynski, Piotr Henryk; Skarżyńska, Magdalena B.; Vieira Biaggio, Eliara Pinto (Frontiers in Psychology, 2024)
Background: Congenital toxoplasmosis (CT) occurs mainly by primary maternal infection during pregnancy. It is estimated that the incidence of vertical transmission to the fetus is 20% and that infected women are more likely to have a premature birth or low birth weight neonate since there is an association between CT and the rate of premature birth and low birth weight. In addition to severe neurological and ophthalmic consequences, hearing disorders are also among the clinical manifestations. The objective of this study is to verify what are the auditory disorders seen in children with CT.Methods: This literature review was structured according to the PRISMA statement and based on the terms of PICOS. Electronic databases were consulted: PubMed, Web of Science, Scopus, and Lilacs. The combined terms were: ("auditory evoked potentials" OR "hearing" OR "hearing loss") AND ("congenital toxoplasmosis"). The selection was carried out independently, blindly, by two of the authors, to minimize risk of bias.Results: The search identified 172 articles From the selection made by reading the titles and abstracts. 12 studies were included in the final analysis. A significant percentage of studies sought to study the peripheral auditory pathway, verifying the occurrence or association between hearing loss and the presence of congenital infection. Only two studies evaluated the central auditory pathway. Conclusion: Toxoplasmosis affects not only the peripheral areas but central areas as well. Most studies suggest this pathology as a risk factor for both peripheral and central impairment. Research has found a greater association between CT and mild to moderate hearing loss, in addition to alterations in exams such as BAEP and FFR. These data recommend that CT be reported as a global public health problem and can help assess complications and impacts of hearing disorders as a result of CT. There is a gap about studies that retract the co-occurrence between CT and other Risk Indicators for Hearing Loss (RIHL), such as prematurity and permanence in the intensive care unit , lack of longitudinal studies, that accompany the development of hearing and language of children with CT, since the consequences of this infection may be late.